DIVERSITY OF EPIPHYTIC ORCHIDS AND HOST TREES (PHOROPHYTES) IN SECONDARY FOREST OF COBAN TRISULA, MALANG REGENCY, EAST JAVA, INDONESIA - Siti Nurfadilah (BIOTROPIA, 2015)
Epiphytic orchids are an integral component of forest ecosystems and contribute significantly to plant diversity. The aim of this study was to investigate the diversity of orchids and their host trees (phorophytes) in a secondary forest at Coban Trisula (the Trisula Waterfall), Bromo Tengger Semeru National Park, East Java Province, Indonesia. Two line transects were established, each 150 m long and consisting of ten 10 × 10 m plots, resulting in a total of 30 sampling plots at the study site. The following data were recorded in each plot: species names and number of individuals of epiphytic orchids, species names and number of individuals of phorophytes, and the vertical distribution of orchids on the phorophytes. A total of 15 epiphytic orchid species from 13 genera were recorded in the secondary forest of Coban Trisula. Appendicula angustifolia was the most abundant epiphytic orchid species (relative abundance = 52.4%), followed by Trichotosia annulata (29.9%). All recorded orchids were found growing on 21 individuals belonging to nine phorophyte species. Castanopsis javanica (mean = 589.5 orchid individuals/tree) and Engelhardia spicata (mean = 425.67 orchid individuals/tree) were the phorophytes hosting the highest number of orchid individuals, respectively. The greatest abundance of epiphytic orchids occurred on the basal and middle parts of the phorophyte branches (zone 3 and zone 4). This study indicates that orchid conservation management is required in Coban Trisula to protect orchid populations from potential human disturbances, as the site serves as a tourist destination.